Antitubercular evaluation of root extract and isolated phytochemicals from Lophira lanceolata against two resistant strains of Mycobacterium tuberculosis - Jeanne Louise Nkot; Dominique Serge Ngono Bikobo; Auguste Abouem A Zintchem; Norbert Mbabi Nyemeck; Esther Del Florence Moni Ndedi; Patrick Hervé Betote Diboué; Dieudonné Emmanuel Pegnyemb; Christian G. Bochet; Ulrich Koert (Taylor & Francis Group, 2018)
Context: The roots of Lophira lanceolata Van Tiegh. Ex Keay (Ochnaceae) have numerous medicinal values in the Central African region. Even though the MeOH extract of the roots has shown antimycobacterial activities, the constituents responsible for this inhibitory activity remain unknown. Objective: Phytochemical investigation of the MeOH root extract of L. lanceolata and determination of the antimycobacterial activities of that extract and constituents against the growth of Mycobacterium tuberculosis. Materials and methods: Column chromatography was used to provide bioactive phytoconstituents. Those compounds were elucidated using MS and NMR spectroscopic data. Antimycobacterial screening of the extract (4.882-5000 µg/mL in DMSO during 24 h at 37 °C) and isolated compounds (0.244-250 µg/mL in DMSO during 24 h at 37 °C) was performed by microplate alamar blue assay (MABA) against two mycobacterial strains. Results: The investigation of L. lanceolata MeOH roots extract provided of mixture of unseparated biflavonoids with a newly described one, dihydrolophirone A (1a) associated to lophirone A (1b). The bioactive compounds that effectively inhibited the growth of M. tuberculosis AC45 were found to be compounds 1 and 2. They exhibited MIC values of 31.25 and 15.75 µg/mL, respectively, and their MIC was found to be 62.5 µg/mL against resistant strain AC83. Discussion and conclusions: It is clearly evident from the results obtained that the mycobacterial activity of L. lanceolata could be related mainly to its steroid and flavonoid contents. Therefore, this study suggests the potential of the above-mentioned classes of compounds as promising candidate agents for developing new anti-tuberculosis drugs.